Perbandingan Penggunaan Caliper Racing dan Kecepatan Terhadap Jarak Pengereman Roda Depan Sepeda Motor Matic 110cc - Adji Nur Permana; Ahmad Hanif Firdaus (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Caliper is an important thing in a vehicle, because at this time there are many caliper brands from domestic and foreign manufacturers with different qualities. Caliper quality affects braking performance. So it takes a caliper that has the best braking performance, many automotive manufacturers introduce calipers with different brands such as domestic or foreign brands, which are no less good quality with original products. The purpose to be achieved in this study is to determine the effect of differences in the type of standard caliper with racing caliper on braking distance and braking time of Scoopy 110 CC motorcycle in order to get which caliper gets better braking performance. The results of the study obtained an average decrease in braking time of 6.27% at a speed of 20 km / h, 6.4% at a speed of 40 km / h, and 6.63% at a speed of 60 km / h and an average decrease in braking mileage of 6.14% at a speed of 20 km / h, 6.24% at a speed of 40 km / h, and 6.34% at a speed of 60 km / h.